THE EFFECT OF TEACHING EDUCATION THROUGH COMPUTER TECHNOLOGIES IN UZBEKISTAN (2017–2027) AND FUTURE PERSPECTIVES TO 2030 - Alimova Hilola; Toshpulatov D.A (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION This article examines the large-scale digital transformation of the education system in Uzbekistan between 2017 and 2027, focusing on the impact of computer technologies on accessibility, quality, management efficiency, and learning outcomes. The study provides statistical analysis of infrastructure expansion, teacher digital competency, student engagement, and the development of national e-learning platforms. It also identifies structural challenges such as digital inequality and regional disparities. Furthermore, the article outlines strategic priorities for 2030, including artificial intelligence integration, adaptive learning systems, full digital infrastructure coverage, and cybersecurity frameworks.